Pengaruh Radiasi Gelombang Elektromagnetik Telepon Genggam Terhadap Perkembangan Sperma - Asep Wahyudi Sudirman (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: Increased use of mobile phones has made users have to pay more attention to the side effects of cell phone use on human health. men who carry a cell phone in a pants pocket can reduce sperm productivity by 70% and even worse the sperm produced will not be able, to fertilize until infertile because it has been damaged by the electromagnetic wave radiation emitted by a cell phone. Objective: to determine the effect of cell phone electromagnetic radiation radiation on sperm development Method: Using literature studies from both national and international journals by summarizing the topic of discussion and comparing the results presented in each article. Results: Exposure to mobile electromagnetic waves can cause increased production of Reactive Oxygen Species (ROS) such as Malondialdehyde (MDA) and decreased antioxidant activity such as catalase, Superoxide Dismutase (SOD) and Gluthatione Peroxidase (GSH). The amount of ROS that exceeds protective antioxidants in the body can cause oxidative stress, cell damage, and tissue. Oxidative stress can increase lipid peroxidation of unsaturated fatty acids in spermatozoa cell membranes. Seminiferous tubular degeneration can also occur due to increased ROS which can cause decreased spermatozoa motility, dysfunction of Leydig cells and Sertoli cells. Conclusion: cell phone use has been proven to have a negative effect on the male reproductive system.